Identification of ZNF217, hnRNP‐K, VEGF‐A and IPO7 as targets for microRNAs that are downregulated in prostate carcinoma. Issue 4 (3rd August 2012) - Szczyrba, Jaroslaw; Nolte, Elke; Hart, Martin; Döll, Celina; Wach, Sven; Taubert, Helge; Keck, Bastian; Kremmer, Elisabeth; Stöhr, Robert; Hartmann, Arndt; Wieland, Wolf; Wullich, Bernd; et al.
Abstract In primary prostate cancer (PCa), a major cause of cancer‐related death in men, the expression of various microRNAs (miRNAs) is deregulated. We previously detected several miRNAs, for example, miR‐24 and miR‐22, as significantly downregulated in PCa (Szczyrba et al., Mol Cancer Res 2010;8:529‐38). An in silico search predicted that zinc finger protein 217 (ZNF217) and importin 7 (IPO7) were potential target genes of these miRNAs. Additionally, for two genes that are deregulated in PCa (heterogeneous nuclear ribonucleoprotein K, hnRNP‐K, and vascular endothelial growth factor A, VEGF‐A), we identified two regulatory miRNAs, miR‐205 and miR‐29b. The regulation of the 3′‐untranslated regions of the four genes by their respective miRNAs was confirmed by luciferase assays. As expected, the upregulation of ZNF217, hnRNP‐K, VEGF‐A and IPO7 could be verified at the protein level in the PCa cell lines LNCaP and DU145. ZNF217 and IPO7, which had not yet been studied in PCa, were analyzed in more detail. ZNF217 mRNA is overexpressed in primary PCa samples, and this overexpression translates to an elevated protein level. However, IPO7 was upregulated at the protein level alone. The inhibition of ZNF217 and IPO7 by siRNA resulted in reduced proliferation of the PCa cell lines. ZNF217 could thus be identified as an oncogene that is overexpressed in PCa and affects the growth of PCa cell lines, whereas the function of IPO7 remains to be elucidated in greater detail.